Development and validation of a multiple abilities inventory for adolescents with special needs - Salazar, Catalina Santos; Gomez, Marie Grace Avelino; Salubayba, Teodora M.; Muega, Maricris B. Acido; Licuan, Ma. Cecilia D.; Magtoto, Frances Olivia M. (Quezon City College of Education, University of the Philippines Diliman, 2018)
The study aimed to develop and validate a multiple abilities inventory for adolescents with special needs. It purported to provide the students an instrument that they could use to identify their abilities. The sources of the items for the inventory were the topics under each track and strand of the Senior High School Program of the K to 12 Basic Education Program. The following measures were done to provide assurance that each of the 115 statements defined or described a single construct- abilities: 1) a table of specifications based on the tracks and strands was prepared. 2) all the topics in the test blueprint were included in the inventory. 3) the list of functions or descriptions of the occupation involved in the tracks and strands was submitted to a panel of subject matter specialists to assess the accuracy of the work as expressed in the item, where the item describing the work of a teacher, for example, is given to a teacher. 4) items from these lists were assembled, prepared in Filipino, and submitted to a group of seven evaluators to evaluate the items and rate the scale against a set of criteria, such as clarity, correctness, suitability to the Grades 8-9 students' level of understanding, and the accuracy of the translation. 5) the revised scale was pilot tested to one Grade 8 class in a SPED school in Quezon City. This group was selected because it was composed of regular students and those with special needs. The students were asked to identify words which seemed difficult to understand, misspelled, and redundant. 6) the scale was shown to the guidance counselors or school personnel at the schools for the blind, for the deaf, for the crippled, and other student with special needs. The consultation resulted in these changes: delete one item, use an instrument written in English, leave a space for the "Yes" - "No" answers beside the item number. The new scale for the blind was reduced to 105 items, prepared in Filipino, answered "Oo" or "Hindi", using Braille paper and their individual styluses.
Dissertation
Includes bibliographical references (175-190 leaves).
Keywords: Youth with disabilities -- Education -- Philippines; Teenagers with disabilities -- Education -- Philippines; Special education -- Philippines; High school students -- Philippines